HIV/AIDS-related knowledge, attitudes and perceptions of urban Ghanaian pregnant women: Results of a qualitative study - Amoah Adongo, Awinaba; Mensah Dapaah, Jonathan; Addo, Bright (International journal of Africa nursing sciences, 2024)
Knowledge, attitudes, and perceptions (KAPs) regarding HIV/AIDS is one of the cornerstones in the fight against the disease. Mortality and morbidity among HIV-infected pregnant or postpartum women are reported to be eight times higher than their HIV-uninfected counterparts. Preventing mother-to-child transmission (PMTCT) strategies can be more effective if women, particularly pregnant women, have comprehensive knowledge about HIV/AIDS. This qualitative study was designed to explore the knowledge, attitudes, and perceptions of HIV/AIDS among 18 pregnant women attending antenatal care in a health facility in Accra, Ghana. Data was collected through individual in-depth interviews, transcribed and thematically analysed using the six steps identified by Braun and Clarke. Three themes emerged from the analysis: (a) Pregnant women’s knowledge of the causes and transmission of HIV/AIDS, (b) Attitude towards HIV/AIDS and HIV testing, and (c) Perceptions about pregnant women living with HIV. We found the knowledge of the causes and mode of HIV transmission among the pregnant women to be relatively high. However, testing to determine their HIV status was low, owing to factors such as fear of testing positive, the stigma, discrimination, and prejudice associated with HIV/AIDS, and misconceptions some had about how the virus could be contracted (spiritually), which necessitated spiritual assistance before, during, and after testing. The findings underscore the need for health professionals to address myths and superstitions about HIV/AIDS during antenatal care visits to encourage and improve testing uptake among pregnant women.